Impact of Digitized Instructional Materials in Teaching Phonology in the New Normal - Vicente Fernandez (JPAIR Institutional Research Journal)
Audio-visual learning materials can be considered effective tools in enriching the classroom experience for students by giving them the complete experience of observing the situations and processes in a speech class.  The study attempts to determine the utilization of digitized instructional materials on students’ speaking skills. Specifically, it aims to assess the level of mastery of the students’ speaking skill in terms of vowel and consonant sounds and speaking patterns, analyze the problems encountered by the respondents during the utilization of Digitized Instructional Material in speech class, and prepare digitized instructional material in order to improve the speaking skill of the students. The descriptive research method was used to gather the needed data for the study.  The results of the study revealed that the majority of the respondents displayed a good performance in the production of vowel and consonant sounds. The production of rhythm and intonation patterns were classified in the mastery level. It showed that the DIM had a great impact on the speech production of the respondent as they were classified in the mastery level. As recommended, the Digitized Instructional Material in speech class is highly recommended to be used by the learners as production of correct sounds in English classes sometimes is not anymore observed.